Numerical Simulation Study on the Mechanism of Formation of Apical Aneurysm in Hypertrophic Cardiomyopathy With Midventricular Obstruction - Deng, Long; Zuo, Heng; Li, An; Yang, Chun; Huang, Xueying (Frontiers in Physiology, 2021)
Apical aneurysm was observed to be associated with midventricular obstruction (MVO) in hypertrophic cardiomyopathy (HCM). To investigate the genesis of the apical aneurysm, the idealized numerical left ventricular models (finite-element left ventricle models) of the healthy left ventricle, subaortic obstruction, and midventricular obstruction in HCM of left ventricle were created. The mechanical effects in the formation of apical aneurysm were determined by comparing the myofiber stress on the apical wall between these three models (healthy, subaortic obstruction, and midventricular obstruction models). In comparing the subaortic obstruction model and MVO model with HCM, it was found that, at the time of maximum pressure, the maximum value of myofiber stress in MVO model was 75.0% higher than that in the subaortic obstruction model (654.5 kPa vs. 373.9 kPa). The maximum stress on the apex of LV increased 79.9, 69.3, 117.8% than that on the myocardium around the apex in healthy model, subaortic obstruction model, and MVO model, respectively. Our results indicated that high myofiber stress on the apical wall might initiate the formation process of the apical aneurysm.